1989
DOI: 10.4038/jnsfsr.v17i2.8218
|View full text |Cite
|
Sign up to set email alerts
|

The sex pheromone of the brinjal pest, <em>Leucinodes orbqnalis</em> guenee (Lepidoptera) : problems and perspectives

Abstract: Preliminary laboratory studies have shown the presence of pheromones ofLeucinodes orbonalis , the brinjal shoot and pod borer found in Sri Lapka. Bioassay using an olfactometer revealed that the virgin female of L. orbonalis produces a sex pheromone which elicit highest response during the f i s t night. It was also shown that the pheromone production was discontinuous, the maximum production being around 22 : 00-24 :00 hours. Chemical investigations of the pheromone gland contents of calling females showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…the compound was used at the rate of 300-500 and was tested for its efficacy in Sri Lanka. However, the synthetic product was inferior and less effective to live virgin female moths [23]. But, the high number of male moths were trapped by the combination of (E)-11-hexadecenyl acetate and (E)-11hexadecen-1-ol and significantly reduced the pest damage in India and Bangladesh [8,11,17,24].…”
Section: Use Of Sex Pheromonesmentioning
confidence: 99%
“…the compound was used at the rate of 300-500 and was tested for its efficacy in Sri Lanka. However, the synthetic product was inferior and less effective to live virgin female moths [23]. But, the high number of male moths were trapped by the combination of (E)-11-hexadecenyl acetate and (E)-11hexadecen-1-ol and significantly reduced the pest damage in India and Bangladesh [8,11,17,24].…”
Section: Use Of Sex Pheromonesmentioning
confidence: 99%
“…They synthesized this chemical in the laboratory and used at the rate of 300-500 µg per trap to attract the EFSB males in the field. Attygalle et al (1988) and Gunawardena et al (1989) also identified the presence of this compound from the sex pheromone glands of EFSB in Sri Lanka. In addition, they have also identified trace quantities of (E)-11-hexadecen-1-ol (E11-16:OH).…”
Section: Sex Pheromonesmentioning
confidence: 90%
“…E11-16:Ac was synthesized in the laboratory and tested for its attraction in Sri Lanka. Although it attracted male moths in the laboratory, its performance under field conditions was inferior to live virgin female moths (Gunawardena, 1992;Gunawardena et al, 1989). However, E11-16:Ac when used alone or in combination with E11-16:OH attracted significantly high numbers of male moths in India and Bangladesh, although E11-16:OH alone showed no attraction at any concentration (AVRDC, 1996;Srinivasan and Babu, 2000).…”
Section: Sex Pheromonesmentioning
confidence: 99%
“…The use of this chemical @ 300-500 µg per trap attracts the adult males in the field. The pheromone was synthesized in the laboratory and tested for its efficacy in Sri Lanka but the synethtic product was inferior to live virgin female moths (Gunawardena, 1992;Gunawardena et al, 1989). However, combination of chemicals (E)-11-hexadecenyl acetate and (E)-11-hexadecen-1-ol continuously trap high number of male moths on pheromone trap and significantly reduce the pest damage in India and Bangladesh (AVRDC, 1996;Alam et al, 2003;Srinivasan and Babu, 2000;Srinivasan, 2008).…”
Section: Sex Pheromonesmentioning
confidence: 99%